IClick synthesis of network metallopolymers. Issue 48 (29th November 2022) - Shen, Yu-Hsuan; Ghiviriga, Ion; Abboud, Khalil A.; Schanze, Kirk S.; Veige, Adam S.
Abstract : Described is an approach to preparing the first iClick network metallopolymers with porous properties. Abstract : Described is an approach to preparing the first iClick network metallopolymers with porous properties. Treating digoldazido complex 2-AuN3 with trigoldacetylide 3-AuPPh3 or 3-AuPEt3, trialkyne 3-H, tetragoldacetylide 4-AuPPh3, or tetraalkyne 4-H in CH2 Cl2 affords five iClick network metallopolymers 5-AuPPh3, 5-AuPEt3, 5-H, 6-AuPPh3, and 6-H . Confirmation of the iClick network metallopolymers comes from FTIR, 13 C solid-state cross-coupling magic angle spinning (CPMAS) NMR spectroscopy, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and nitrogen and CO2 sorption analysis. Employing model complexes 7-AuPPh3, 7-AuPEt3, 7-H, 8-AuPPh3, and 8-H provides structural insights due to the insolubility of iClick network metallopolymers.